Contemporary Islamic Economic Law on Legal Protection for Bankrupt Guarantors: Comparative Insights from Common Law and Asian Jurisdictions - Bambang Sugeng Ariadi Subagyono; Ermanto Fahamsyah; Hariyanto Sururi; Amaliyah (Faculty of Sharia, IAIN Metro, 2025)
The legal protection of guarantors declared bankrupt or suspended from debt payment obligations (PKPU), together with the principal debtor, remains a critical yet underexplored issue in Indonesian insolvency law. This study examines the scope and adequacy of such protections under contemporary Islamic economic law, providing comparative insights from selected common law and Asian jurisdictions. Employing a normative juridical approach combined with comparative legal analysis, the research analyses statutory provisions, judicial precedents, and doctrinal interpretations. The study highlights the imbalance of liability between guarantors and debtors, the absence of explicit safeguards under Law No. 37 of 2004 on Bankruptcy and PKPU, and the resulting implications for creditor rights and economic justice. Comparative analysis draws from the United Kingdom and United States (standard law systems) and Singapore, Japan, and Malaysia (Asian jurisdictions), revealing more structured protections for guarantors, including mechanisms such as independent liability, automatic stay, and negotiated debt restructuring. The findings indicate that Indonesia's current framework inadequately recognises the secondary and derivative nature of guarantor obligations, exposing them to disproportionate risk. This study contributes to the academic discourse by integrating contemporary Islamic economic principles into the analysis of insolvency law, providing a normative framework for reform and offering comparative insights that can inform both legislation and future research on guarantor protection. The study recommends legislative reform to explicitly regulate guarantor protection, integrating principles of proportionality, good faith, and balanced creditor–debtor relations, in line with contemporary Islamic economic law.